Le bilinguisme dans l'administration fédérale du Canada (1969-1982) - Robichaud, Jacques (Les Cahiers de droit, 1983)
The author first examines the various public declarations which form the basis of the federal government's official languages policy, and then identifies the various stages in the application of this policy to the public service sector. He concludes with an examination of the current situation.